2019
DOI: 10.1002/edm2.47
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic spectrum of polycystic ovary syndrome and their relationship to the circadian biomarkers, melatonin and cortisol

Abstract: Summary Objective Firstly, to investigate whether polycystic ovary syndrome (PCOS) shows a continuum of severity with increasing number of phenotypic features comprising the Rotterdam criteria for PCOS and secondly, to explore relationships of these phenotypes to the circadian biomarkers, cortisol and melatonin. Background Studies characterizing the spectrum of PCOS subphenotypes give little emphasis to the distinction among women who manifest zero, one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…It has been reported long ago that melatonin rhythms are disrupted in night shift workers [79]. Similar disruption was found in women with PCOS [80][81][82][83].…”
Section: Melatonin Clock Genes and Gonadotropins Disruption: The Case Of Pcossupporting
confidence: 69%
“…It has been reported long ago that melatonin rhythms are disrupted in night shift workers [79]. Similar disruption was found in women with PCOS [80][81][82][83].…”
Section: Melatonin Clock Genes and Gonadotropins Disruption: The Case Of Pcossupporting
confidence: 69%
“…PCOS is a disease with complex etiology affecting 6–7% of adult women ( Franks, 2008 ). Recently, many studies have indicated that biological clock genes are associated with the development of PCOS ( Li et al, 2011 ; Lim et al, 2019 ). A study by Li et al (2011) , identified that a polymorphism in Melatonin receptor 1A ( MTNR1A ) gene, a regulator of circadian rhythm, is associated with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Li et al (2011) , identified that a polymorphism in Melatonin receptor 1A ( MTNR1A ) gene, a regulator of circadian rhythm, is associated with PCOS. Studies have identified a dysregulation in biological clock factors such cortisol ( Lim et al, 2019 ), per2, and clock ( Chen et al, 2016 ) to be highly correlated with an incidence of PCOS. However, till date the molecular mechanism associating biological genes to PCOS is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive evidence synthesis and review process required for guideline formulation highlighted that each diagnostic criteria constitutes a continuum. 20,21 Specific cut-offs or thresholds are most often arbitrarily defined and are often based on an arbitrary percentiles assessed in variably defined populations, 10,22,23 limiting the accuracy and validity of the PCOS diagnosis. The guideline process improved diagnostic accuracy by prioritizing defining cut-off for each of the diagnostic features.…”
Section: Diagnosis Of Polycystic Ovary Syndromementioning
confidence: 99%